New Nanocomposite Membranes with blended Sulfonated Poly-Eugenol (S-PE) and Titanium Dioxide (TiO2) as an alternative in Direct Methanol Fuel Cells - Muliawati, Eka Cahya (Institut Teknologi Adhi Tama Surabaya, 2024)
This study fabricated a novel sulfonated poly-eugenol/titanium dioxide nanocomposite membrane as an alternative polymer electrolite membrane (PEM) to direct methanol fuel cells (DMFCs), addressing the high cost of PEM, a major challenge for fuel cell (FC) commercialization. Sulfonated poly-eugenol (S-PE), synthesized by polymerizing eugenol with sulfuric acid, incorporated sulfonic acid groups to improve proton flows conductivity. Titanium Dioxide nanoparticles were incorporated into the sulfonated polymer matrix, forming a mixed membrane nanocomposite. Scanning electron microscopy confirmed a homogeneous TiO2 distribution in the polymer. The membranes' physicochemical properties, including air absorption, swelling, and methanol absorption, were evaluated and compared to commercial Nafion. The S-PE and TiO2nanocomposite membrane with 25% (S-PE) and 5% TiO2 exhibited higher water and methanol absorption than Nafion, but lower proton conductivity. However, its low methanol permeability can potentially improve fuel efficiency in direct methanol fuel cells. Incorporating TiO2 into sulfonated poly-eugenol represents a promising strategy for developing low-cost, efficient PEM for DMFCs applications.